If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + -2y = -1 Solving 24x + -2y = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 24x + -2y + 2y = -1 + 2y Combine like terms: -2y + 2y = 0 24x + 0 = -1 + 2y 24x = -1 + 2y Divide each side by '24'. x = -0.04166666667 + 0.08333333333y Simplifying x = -0.04166666667 + 0.08333333333y
| X+8-4x+8x=7x+9+5x-2 | | 9-(1-3y)=48+y-(3-y) | | 2x-5/-45/4 | | x^2+7*x+29=0 | | (8x+5)-20x=x | | -5(2/3)=(2/3)-6(2/3)= | | -5*2/3= | | 2y-6+3x=0 | | -5(2/3)= | | 7x+5y-3x-8y=1 | | 18y+x=28-3y | | x*x-5=126 | | 2b+3a=1.4 | | X/2=-15=x/5 | | 7y+5=20 | | 4/18=5/x | | 100/x=y | | 22-3(x-2)=2(4+x) | | x+x+x-5y-y-3x= | | 12x+3=-2b-4 | | -4x-4x-7y= | | x^2+3x+4-sqrt(x^2+3x+6)=0 | | 8x^6=2x^2 | | 8x^6=4x^2 | | 3z+6x-5z+2x= | | x^2+3x+4=sqrt(x^2+3x+6) | | 24x+44+55x=55x+64x | | 0.2(b-2)-0.5(b+2)=4.5 | | -16t^2+128t-192=0 | | 6k^2+7k-4-7k^2-11k+4= | | 8-2/p-1=2 | | [4x]-3=-7 |